Photoelectron spectroscopy in molecular physical chemistry. Issue 4 (13th January 2022) - Fischer, Ingo; Pratt, Stephen T.
Abstract : Photoelectron spectroscopy has evolved into a powerful tool for physical chemistry and molecular physics. Some recent examples are highlighted in this perspective. Abstract : Photoelectron spectroscopy has long been a powerful method in the toolbox of experimental physical chemistry and molecular physics. Recent improvements in coincidence methods, charged-particle imaging, and electron energy resolution have greatly expanded the variety of environments in which photoelectron spectroscopy can be applied, as well as the range of questions that can now be addressed. In this Perspectives Article, we focus on selected recent studies that highlight these advances and research areas. The topics include reactive intermediates and new thermochemical data, high-resolution comparisons of experiment and theory using methods based on pulsed-field ionisation (PFI), and the application of photoelectron spectroscopy as an analytical tool to monitor chemical reactions in complex environments, like model flames, catalytic or high-temperature reactors.